2022
DOI: 10.1038/s41398-022-01877-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing mood disorders in the AFFECT study: a large, longitudinal, and phenotypically rich genetic cohort in the US

Abstract: There has recently been marked progress in identifying genetic risk factors for major depression (MD) and bipolar disorder (BD); however, few systematic efforts have been made to elucidate heterogeneity that exists within and across these diagnostic taxa. The Affective disorders, Environment, and Cognitive Trait (AFFECT) study presents an opportunity to identify and associate the structure of cognition and symptom-level domains across the mood disorder spectrum in a prospective study from a diverse US populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 78 publications
0
10
1
Order By: Relevance
“…Typical control study participants were recruited from the 23andMe, Inc. database as part of the AFFECT study (Dalby et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical control study participants were recruited from the 23andMe, Inc. database as part of the AFFECT study (Dalby et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Typical control study participants were recruited from the 23andMe, Inc. database as part of the AFFECT study (Dalby et al., 2022 ). Participant eligibility criteria were: age between 18 and 50 years upon enrolment, residence in the United States, access to a desktop or laptop computer, and no reported diagnosis of Parkinson's disease, essential tremor, Schizophrenia, Alzheimer's disease, bipolar depression, major depression, generalized anxiety disorder, or PTSD as well as never having been prescribed an antidepressant, mood stabilizer, or antipsychotic medication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-reported sample was obtained from an observational 23andMe Inc. study, named the AFFECT study [ 18 ] of 18,811 European participants with a self-reported diagnosis of depression or bipolar disorder by a medical professional and medication status data. The study included 642 study participants of European genetic ancestry who had received vortioxetine within the past five years and had rated the response from 0 (not at all) to 4 (a great deal).…”
Section: Methodsmentioning
confidence: 99%
“…Motivated by this, the aim of this study was to assess PRSs associations with placebo and antidepressant treatment response from pooled clinical trial data and test its generalizability to real-world data from a web-based survey conducted by 23andMe Inc. [ 18 ]. We use a deep clinical test sample ( N = 1364) with vortioxetine and placebo-treated patients and a self-reported test sample with vortioxetine-treated patients ( N = 642).…”
Section: Introductionmentioning
confidence: 99%